Production and the Real Rate of Interest: A Sample Path Equilibrium - Feldman, David (Review of Finance, 2001)
Abstract This paper examines a multiperiod production economy where investors do not observe the realizations of productivity factors or security expected returns. Unlike previous work, which expresses the equilibrium conditions as functions of unobservable (to both real-world investorsand empiricists) moments of the distributions of returns, we express the equilibrium real rate asa function of the observable sample paths of realizations of returns. We provide a framework for empirically testing this and other asset pricing models without outside-the-model econometric assumptions needed for producing the unobservable moments of returns. We construct versions of the restrictions for any time interval between observations. JEL codes: E43, G12, D92, D80, D51